1970
DOI: 10.1017/s0021859600026046
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of dietary fats by ruminants:I. The digestibility of some commercially available fats

Abstract: SUMMARYThe digestibility of some fats (beef tallow, HEF, herring oil, soyabean oil and maize oil) were studied in balance trials with sheep which had been maintained on the diets for a 35 day period of acclimatization to establish ‘steady state’ conditions. Corrected digestibility coefficients for the individual fats were calculated from a knowledge of the intake and output of lipid on a low-fat basal ration. The difference between the intake of fat and the corrected lipid output (total lipid output minus lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

1976
1976
1996
1996

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 17 publications
4
19
0
1
Order By: Relevance
“…In ileal chyme, the relative proportion of stearic acid increased (P < .01) linearly with level of fat supplementation, suggesting that the digestibility of this fatty acid was reduced as a result of level of supplementation. This observation is consistent with other studies (Lennox and Garton, 1968;Andrews and Lewis, 1970) that have demonstrated comparatively lower rates of digestion for stearic acid.…”
Section: Z1nnsupporting
confidence: 93%
See 1 more Smart Citation
“…In ileal chyme, the relative proportion of stearic acid increased (P < .01) linearly with level of fat supplementation, suggesting that the digestibility of this fatty acid was reduced as a result of level of supplementation. This observation is consistent with other studies (Lennox and Garton, 1968;Andrews and Lewis, 1970) that have demonstrated comparatively lower rates of digestion for stearic acid.…”
Section: Z1nnsupporting
confidence: 93%
“…In light of the extensive biohydrogenation of fatty acids in the rumen and the consistent observation that palmitic acid had a higher intestinal digestibility than stearic acid (Andrews and Lewis, 1970;Johnson and Leibholz, 1980), it appears that one practical index of the feeding value of blended fats is a high palmitic acid concentration.…”
Section: Z1nnmentioning
confidence: 99%
“…To compensate for the high ratio of saturated FA in the fat flowing to the intestines, ruminants generally digest saturated FA better than non-ruminants (Andrews & Lewis, 1970a;Andrews & Lewis, 1970b). However, also for ruminants intestinal digestibility of unsaturated FA is higher than for saturated FA (Hagemeister & Kaufmann, 1979), which is most obvious when the ratio of saturated to unsaturated FA is high (Mdler & Barsting, 1987).…”
Section: Fatty Acid Digestibilitymentioning
confidence: 99%
“…Moreover, the digestibility of such lipids in the small intestine appears high (Andrews and Lewis, 1970 Concentration and composition of VFA in rumen fluid were determined by GLC (Jouany, 1982).…”
Section: Introductionmentioning
confidence: 99%